Dissolving a Partnership Efficiently. - Cramton, P; Gibbons, R; Klemperer, P (1987)
Several partners jointly own an asset that may be traded among them. Each partner has a valuation for the asset. The valuations are known privately and drawn independently from a common probability distribution. The authors characterize the set of all incentive-compatible and interim individually-rational trading mechanisms, and give a simple necessary and sufficient condition for such mechanisms to dissolve the partnership ex post efficiently. A bidding game is constructed that achieves such dissolution whenever it is possible. Despite incomplete information about the valuation of the asset, a partnership can be dissolved ex post efficiently provided no single partner owns too large a share.